THE IMPLEMENTATION OF SYSTEM DYNAMICS IN HOSPITAL SERVICES FOR IMPROVING THE INPATIENT ROOMS UTILIZATION - Heri Supriyanto; Erma Suryani (Universitas Trunojoyo Madura, 2019)
Hospitals are an important part of the health system. This agency consists of several main services, namely Outpatient, Emergency, and Inpatient services. One type of main service that is quite complex and needs to be considered is service at inpatient installations. Regarding this inpatient service, hospitals must make a structural and functional utilization effort to be further improved by increasing the utilization of service space regarding the number of available beds. To measure the level of utilization of hospital facilities at inpatient services, hospital service indicators are needed to measure it. These indicators include BOR (Bed Ocupanccy Rate), which is the percentage of beds filled, LOS (Length of Stay), namely the average length of stay, TOI (Turn Over Interval), which is the average free time of bed, BTO (Bed Turn Over), namely the productivity of the bed. These indicators will be presented in graphical form, namely Barber Johnson Graph. From the values ​​produced by the hospital management, later it can be used as material for planning and decision-making in determining service facility policies in the future. The purpose of this study is to make modeling with a system dynamics so that the value of the indicator can have ideal parameter values. The result of this study is that a scenario is needed to increase the number of patient visits, because patient visits are too low. This is evidenced by the value of the BOR which is less than the ideal value. In addition, the duration of patient care, day of care was influenced by the variable number of patient visits. The results of the scenario show that in 2019 to 2030 the values ​​of BOR, LOS, TOI, and BTO were produced according to the ideal indicator value. Keywords: Inpatients, Room Utilization, Service Indicators, System Dynamics.